Determinants of Anemia among Children Aged 6–59 Months Living in Kilte Awulaelo Woreda, Northern Ethiopia - Gebremedhin Gebreegziabiher; Belachew Etana; Daniel Niggusie (Anemia)
Introduction. The aim of this study was to determine the prevalence of anemia and determinant factors among children aged 6–59 months living in Kilte Awulaelo Woreda, eastern zone. Method. A community based cross-sectional study was conducted during February 2013 among 6 tabias of Kilte Awulaelo Woreda, northern Ethiopia. A total of 568 children were selected by systematic random sampling method. Anthropometric data and blood sample were collected. Bivariate and multivariate logistic regression analyses were performed to identify factors related to anemia. Result. The mean hemoglobin level was 11.48 g/dl and about 37.3% of children were anemic. Children who were aged 6–23 months [AOR = 1.89: 95% CI (1.3, 2.8)], underweight [AOR = 2.05: 95% CI (1.3, 3.3)], having MUAC less than 12 cm [AOR = 3.35: 95% CI (2.1, 5.3)], and from households with annual income below 10,000 Ethiopian birr [AOR = 4.86: 95% CI (3.2, 7.3)] were more likely to become anemic. Conclusion. The prevalence of anemia among the children is found to be high. It was associated with annual household income, age, and nutritional status of the child. So, improving family income and increasing awareness of the mother/caregiver were important intervention.